BULLYING IN JENNIFER NIVEN’SALL THE BRIGHT PLACES - Rosa Maria Simamora; Bonar Gurning; Abigail Victoria L. Tobing (Muse: Jurnal of Art, 2025)
This article describes bullying in Jennifer Niven's All the Bright Places. In this novel, Niven clearly presents Finch, the main character of the story, as a representation of people who becomes the victim of bullying by his father and his school community and end in commiting suicide. This study uses narrative qualitative research and applies literary sociology theory by Wellek and Warren saying that the work of literature, the purpose as well as the things that are implicit in the work itself and that are related to social problems. The analysis is focused on bullying of Finch, the main character of the novel, who committed suicide because he had been bullied physically, verbally and cyberly at home and school. Physical bullying is represented by Finch's father and Roamer. Verbal bullying is represented by Finch's father, Roamer, Amanda Monk, and his other school-mates. Cyberbullying is represented by his school community. He feels no one likes him or understands his feelings neither his parents nor his school community. In conclusion, Jennifer Niven in All the Bright Places vividly and beautifully conveys a moral message about bullying and its effect on people which leads to suicide.